The Impact of Nurses Training and Competence on the Quality of Inpatient Services in Bandung Hospital - Ade Sudrajat; Dyah Bayu Framesthi (Universitas Padjadjaran, 2024)
By using an explanatory descriptive research design, this study proposes to measure the influence of nurse training and competence on service quality. This research used field studies and literature observations, as well as conducting observations, interviews, and distributing questionnaires to 31 respondents of nurses and patients who utilize the service. Research and data analysis show that training affects service quality by 0.756, competency affects service quality by 0.491, and training and both together affect service quality by 0.805 and the rest is influenced by additional factors that were not researched. When viewed from its dimensions, training and competency have a very good and significant influence on the quality of inpatient services at Bandung (city) Hospital. As a result, good service quality can be achieved, one strategy that can be taken is to improve the quality of human resources through providing training and continuously increasing the competency of nurses.